Interactive Technologies in the Art Museum - Pam MeeCham; Elena Stylianou (Stockholm University Press, 2012)
When in June 2013 The Guardian newspaper (UK) asked us to 'help create the whole picture' with the GuardianWitness app ('upload your part of the story faster with 4GEE at witness.guardian.co.uk') we know the citizen reporter and the eyewitness photographer have been allied to faster, participation and the double page spread (The Guardian, Saturday 06.07.13 pp 2 and 3). Undermining the authorship, authority and arguably the professionalism of the journalist and photographer, the amateur enthusiast, key eye-witness or commentator are crowd-sourced to open up, enhance and create a whole, diverse picture of world events that, in the advertisement at least, speaks of a change in the relationship of passive consumer to traditional authorities such as newspapers.